Studi Analisis Terhadap Urgensi dan Implementasi Undang-Undang Nomor 8 Tahun 2010 Tentang Tindak Pidana Pencucian Uang - Ilham Ramadhan; Mia Puspita Sari; Nedi Aprizal; Tyo Qhoirun Nisa; Dimas Dwi Arso (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
This study is entitled Study Analisys of the Urgency and Implementation of the Law Number 8 of 2010 on Prevention and Punishment of Money Laundering. The development of the financial sector in Indonesia continues to progress, but the legal process has not followed the guidelines set by the Indonesian Financial Law and Regulations on Unlawful Money Transfer. Indonesia has enacted several laws to address this problem, including Financial and Material Law Number 8 of 2010, which aims to maintain economic stability and the integrity of the financial system, promote social harmony, economic growth, and government reform. The Indonesian government has implemented various measures to eradicate money laundering, including bilateral and multilateral forums, the concept of double crime, and the implementation of the "KYC" principle. The government also imposes fines on those who break the law, such as fines, jails, and non-bank fines. In the end, money laundering in Indonesia can be effectively managed through legal action and international cooperation. This research uses normative research methods, using non-fiction data sources, electronic journals, legislative regulations, and other relevant library sources to conduct research. The purpose of this research is to find out the urgency of Law Number 8 of 2010 on the Prevention and Eradication of TPPU and what efforts are being made to prevent and eradicate TPPU.